Metode Qira Ah Muwahhadah dalam Membentuk Keserasian Bacaan Al Qur An (Studi Kasus di Pondok Pesantren Madrasatul Qur An (Mq) Tebuireng Jombang) - Moch. Sya’roni Hasan (FALASIFA : Jurnal Studi Keislaman, 2019)
The implementation of the Qira ah Muwaḥḥadah Method is expected to be able to form the reading of Al Qur an santri Madrasatul Qur an Tebuireng which were originally influenced by dialects from each region to be harmonious in accordance with the Qira ah standard taught by K.H.M. Yusuf Masyhar. Based on the background above, this thesis is focused on three aspects of description, namely: 1) learning planning of Qira ah Muwaḥḥadah in Islamic Boarding School Madrasatul Qur an Tebuireng 2) the learning process of Qira ah Muwaḥḥadah in Islamic Boarding School Madrasatul Qur an Tebuireng 3) evaluation of learning Qira ah Muwaḥḥadah at the Islamic Boarding School Madrasatul Qur an Tebuireng. This study states that the implementation of the Qira ah Muwaḥḥadah method includes: classical fas} ah} ah development, Al Qur'an payment, and Al Qur'an memorization. Evaluation of the learning of the Qur'an Qira ah Muwaḥḥadah carried out as a whole, both evaluations that are formal (the Qur'anic test) which is carried out every 6 months and evaluations relating to the learning process of the Qur'an Qira ah Muwaḥḥadah every month. The results of the Qira ah Muwaḥḥadah method at the Madrasatul Qur an Tebuireng Islamic Boarding School can form the Qur'anic readings of the students who were originally influenced by their respective regional dialects to be harmonious according to the Qira ah standard taught by K.H. M. Yusuf Masyhar, so that students of the Islamic Boarding School in Madrasatul Qur an Tebuireng can practice the reading of the Qur'an in their respective regions. Criteria for harmony in reading the Qur'an include: harmonious in the field of proficiency in saying makharijul h} uruf, harmonious in the practice of tajwid when reading the Qur'an and be harmonious in rhythm or song when chanting the verses of the Qur'an.